2020
DOI: 10.1103/physrevb.101.201402
|View full text |Cite
|
Sign up to set email alerts
|

Negative longitudinal magnetoconductance at weak fields in Weyl semimetals

Abstract: Weyl semimetals are topological materials that provide a condensed-matter realization of the chiral anomaly. A positive longitudinal magnetoconductance quadratic in magnetic field has been promoted as a diagnostic for this anomaly. By solving the Boltzmann equation analytically, we show that the magnetoconductance can become negative in the experimentally relevant semiclassical regime of weak magnetic fields. This effect is due to the simultaneous presence of the Berry phase and the orbital magnetic moment of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
3
25
1
Order By: Relevance
“…Therefore, the MR (∝ B 2 m 2 ) induced by the Berry curvature through the OMM effect in the massive nodalline semimetal is opposite in sign to that of the Weyl semimetal (in the absence of inter-node scattering) [18,24] and the topological insulator [63]. Note that the OMM induced deformation of the Fermi surface also introduces a positive correction to the MR in the Weyl semimetal [24], which is in agreement with our results.…”
Section: B Slight Fermi Torus Deformation and Positive Mrsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the MR (∝ B 2 m 2 ) induced by the Berry curvature through the OMM effect in the massive nodalline semimetal is opposite in sign to that of the Weyl semimetal (in the absence of inter-node scattering) [18,24] and the topological insulator [63]. Note that the OMM induced deformation of the Fermi surface also introduces a positive correction to the MR in the Weyl semimetal [24], which is in agreement with our results.…”
Section: B Slight Fermi Torus Deformation and Positive Mrsupporting
confidence: 91%
“…The benefit of this scenario is that the relevant physical effects can be visibly revealed by the MR measurement. For example, it was shown recently that the coupling of the OMM to the magnetic field in the Weyl semimetal induces a deformation of the Fermi surface from a sphere to an egg shape [24]. As a result, the negative MR due to the chiral anomaly can even have the opposite sign as the inter-node scattering is taken into account simultaneously [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More rigorous approaches, developed in Refs. [50][51][52][53] and others, can be used to include the field dependence in the scattering time. This remains as a future direction for us to explore NL magneto-resistivity after including the electric field dependence of the scattering timescale, along with skew-scattering.…”
Section: Discussionmentioning
confidence: 99%
“…In the weak magnetic field regime, it was believed that the LMC is positive [57][58][59][60][61][62][63][64], however a recent study by Knoll et al (Ref. [65]) has now shown that unlike the earlier claims, the LMC can be negative for sufficiently strong intervalley scattering when orbital magnetic moment (OMM) effects are included. While Ref.…”
Section: Introductionmentioning
confidence: 94%